Serum procalcitonin levels together with clinical features and inflammatory markers in women with tubo-ovarian abscess for discriminating requirements for surgery for full recovery - KARACA, KENAN; KARACA, KENAN; özkaya, enis; Eken, Meryem Kurek; uygun, ilgi; Kopuk, Sule Yildirim; alpay, murat (My University, 2018)
Tubo-ovarian abscess (TOA) coexists in 15% of cases with pelvic inflammatory disease. Medical treatment is the first line of approach in women with TOA, however, 25% of cases fail to respond to antibiotics, therefore, these cases need to undergo surgical intervention. We aimed to determine factors leading to failure of medical treatment in women diagnosed with TOA. According to our results among 144 women, 27 cases required surgical intervention for full recovery. None of the demographic, sono-graphic or laboratory findings, including procalcitonin level, had significant predictive value for the failure of medical treatment in women with TOA.